An environmental signature for 323 microbial genomes based on codon adaptation indices - Willenbrock, Hanni (BioMed Central, 2006)
The correlation of two methods for estimating codon adaptation indices applied to more than 300 bacterial species shows that codon usage preference provides an environmental signature by which it is possible to group bacteria according to their lifestyle